VD_FINDINFO HC / 2014 / 489 vom 13. Mai 2014 - VD Tribunal cantonal (2014)
OBLIGATION D'ENTRETIEN, ENFANT NÉ HORS MARIAGE, RELATIONS PERSONNELLES | 275 al. 1 CC, 279 CC, 285 al. 1 CC, 308 al. 1 let. b CPC (CH)